A nexus between active and passive control methods for reduction of aerodynamic noise of circular cylinder. (15th June 2021) - Souri, Mohammad; Mojra, Afsaneh
Highlights: A new combined method of rotating and passive jet was introduced. Sound pressure level was reduced by rotating cylinder and flow injection to the downstream of the cylinder by passive jet. Vortex shedding and Karman Vortex Street were eliminated by the applied methods. Fluctuations were dramatically reduced in the cylinder wake region. Abstract: Today, the status of wildlife is extremely worrying because of noise pollution caused by aerodynamic noise of various industries. Circular cylinders are the most used devices in industries. Therefore, in this study, the aerodynamic noise prediction of circular cylinders is performed using Ffowcs Williams-Hawkings acoustic analogy. The simulation is performed using a 2D URANS model and combines active and inactive methods to control the flow. Our study encompasses the novelty of implementing passive-jet as a passive method with varying numbers of passive suction/blowing holes. Furthermore, in order to play the role of active methods, a rotating cylinder at different rotation frequencies is used, which is combined with the proposed passive method. Results show that the active method reduces the aerodynamic noise by 22 dB, when the frequency is twice the vortex shedding frequency; whereas, the passive jet reduces the noise by 50 dB when the ring is completely composed of suction/jet holes. As a more interesting idea, the two methods are combined to achieve a notable noise reduction of about 56 dB. Meanwhile, results show that the mean drag coefficient, lift fluctuation and Strouhal number are dramatically reduced. The presented methods may not be economically ideal, but they can be used as attractive ideas to optimize applications in the marine and wind industries. Graphical abstract: Image, graphical abstract